(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2006)
This essay utilises one of the many ideas contributed by Professor Danie Strauss towards the development of the Reformational Philosophy based upon the systematic philosophy of Herman Dooyeweerd. It takes up the idea that all analogical moments in the (ontic) aspects of cosmic reality, as articulated in Dooyeweerd’s theory of the modal aspects, have a “modal seat” which is frequently to be found in the non-normative (“natural”) aspects. This idea is applied to explain the concept of jural integrity within the context of Ronald Dworkin’s legal theory of law as integrity. The essay explains the distinction between the moral and jural concepts of integrity whilst leaving open the possibility suggested by Professor Strauss that integrity in the law could also be employed in a moral “idea” way to ethically deepen the law through the ethical “anticipations” that “open up” the concept of law in the idea of justice.